Usefulness of sectoral means in financial analyses of enterprises - Edyta Mioduchowska-Jaroszewicz (e-Finanse: Financial Internet Quarterly, 2019)
Aim: The aim of the paper is to assess the usefulness of sectoral means in financial analyses of enterprises. Research methods: The article uses a deductive approach to assess the suitability of sectoral means used in analyses of t financial standing of enterprises. The method of analysis and logical construction was used for literature review. The methods of descriptive statistics such as arithmetic means, standard deviation and coefficient of variation were used in order to analyze the data and draw conclusions based on the results. Contribution: The assessment of the usefulness of sectoral means in the context of their variability seems to be a crucial aspect for the analysis of a company's financial situation. When assessing the financial standing of an enterprise, it is necessary to use a comparative analysis method, based on, inter alia, a comparison in space. This type of comparison requires the use of sectoral means, whose assessment is extremely important to drawing reliable and correct conclusions regarding the financial situation of a company.
Keywords: G32; 330; financial analysis; coefficient of variation; sectoral ratios; financial ratios